Brief Report: A Novel ELANE Mutation Associated With Inflammatory Arthritis, Defective NETosis, and Recurrent Parvovirus Infection. Issue 12 (8th November 2017) - Thanarajasingam, Uma; Jensen, Mark A.; Dorschner, Jessica M.; Wampler Muskardin, Theresa; Ghodke‐Puranik, Yogita; Purmalek, Monica; Eliopoulos, Elias; Zervou, Maria I.; Goulielmos, George N.; Howard, Matthew; Kaplan, Mariana J.; Niewold, Timothy B.
Abstract : Objective: We describe a 38‐year‐old woman who presented with a history of inflammatory arthritis, rash, and daily fevers. She was noted to have chronic parvovirus infection with persistently detectable viral titers and a novel mutation in the ELANE gene. ELANE encodes neutrophil elastase, a neutrophil serine protease with important antimicrobial effects, and is found as part of neutrophil extracellular trap (NET) complexes. Pathogenic ELANE mutations have been identified in forms of hereditary neutropenia. However, our patient never had neutropenia. Because of the striking clinical scenario, we investigated this mutation functionally. Methods: NET formation by neutrophils was assessed by scanning electron microscopy. Neutrophil activation and neutrophil elastase production were evaluated by flow cytometry and fluorescent substrate–based functional assay, respectively. A multiplex assay was used to quantitate neutrophil inflammatory cytokine production. PyMOL software was used to generate 3‐dimensional models of mutant elastase. Results: Activated neutrophils from the patient demonstrated a significantly decreased ability to form NETs on scanning electron microscopy, as well as quantitative defects in neutrophil activation and neutrophil elastase activity. The patient's neutrophils showed altered levels of interleukin‐12 (IL‐12) and IL‐8, which are key cytokines for antiviral immunity and neutrophil chemotaxis. Three‐dimensional mapping revealed that the mutation could alter protein folding and surface charge distribution, potentially perturbing protein trafficking. Thus, the mutation could affect neutrophil function by decreasing NETosis and altering key antiviral activities of neutrophils. Conclusion: This is the first report of a human pathogenic ELANE mutation associated with a defect in NETosis and a distinct syndrome of recurrent viral infection and chronic inflammation.